Differences in the Characteristics and Business Performance of Street Vendors across Six Locations in the Malik Ibrahim Asmoro Qondi Religious Tourism Area, Tuban - Al-Fatih Maulana; Armawati Hidayati; Ahmad Faizulloh (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study examined differences in the characteristics and business performance of street vendors across six locations in the Malik Ibrahim Asmoro Qondi religious tourism area, Tuban. A quantitative survey design was employed. From a population of 260 vendors, 155 respondents were selected through proportional random sampling. Data were collected through interviews, observation, and documentation, then analyzed using descriptive statistics and one-way ANOVA. The results showed that vendors differed in gender, educational level, merchandise type, trading facilities, source of goods, business duration, working hours, location preferences, capital, turnover, and profit. Vendors operating east of the terminal recorded the highest average daily turnover and profit, whereas those along the entrance road to the tomb recorded the lowest. Turnover differed significantly across the six locations, while profit patterns also varied descriptively. Best-selling products differed by location, including rice meals, instant food and beverages, fruit, accessories, snacks, and local souvenirs. These findings confirm that spatial location, visitor movement, competition, and product suitability shape the performance of informal businesses in religious tourism areas more broadly.